Diurnal changes of colonic motility and regulatory factors for colonic motility in Suncus murinus. Issue 6 (30th November 2021) - Kobayashi, Yuki; Takemi, Shota; Sakai, Takafumi; Shibata, Chikashi; Sakata, Ichiro
Abstract: Background: The aim of this study was to investigate the fundamental mechanisms of colonic motility in the house musk suncus ( Suncus murinus ) as an established animal model of gut motility. Methods: To measure gut motility in free‐moving conscious suncus, strain gauge force transducers were implanted on the serosa of the colon and gastric body. Key Results: We recorded diurnal changes in colonic motility and observed the relationship between feeding and colonic motility. Giant migrating contractions (GMCs) of the colon were invariably detected during defecation and tended to increase during the dark period, thereby indicating that colonic motility has a circadian rhythm. Given that GMCs in the suncus were observed immediately after feeding during the dark period, we assume the occurrence of a gastrocolic reflex in suncus, similar to that observed in humans and dogs. We also examined the factors that regulate suncus GMCs. Intravenous administration of 5‐HT (100 µg/kg), substance P (10 and 100 µg/kg), calcitonin gene‐related peptide (10 µg/kg), and α2 adrenergic receptor antagonist yohimbine (0.5, 1, and 3 mg/kg) induced GMC‐like contractions, as did intragastric and intracolonic administration of the transient receptor potential vanilloid 1 agonist, capsaicin (1 mg/kg). Conclusions & Inferences: These results indicate that the fundamental mechanisms of colonic motility in suncus are similar to those in humans and dogs, and we thus propose that suncus could serve as a novel small animal model for studying colonic motility. Abstract : In order to gain a better understanding of the fundamental mechanisms associated with colonic motility in suncus ( Suncus murinus ), we monitored colonic motility for 24 h along with feeding behavior and defecation in free‐moving conscious suncus. We found that giant migrating contractions occurred immediately prior to defecation, with giant migrating contractions and defecation on average being observed 5.4 times during the light period and more frequently at 15 times during the dark period.